Marketing Education for Sustainable Development - Hübscher, Chiara (2023)
Hübscher, C., Hensel-Börner, S., & Henseler, J. (2024). Marketing Education for Sustainable Development. Spanish Journal of Marketing - ESIC, 28(3), 310-333. https://doi.org/10.1108/SJME-06-2022-0131 --- Funding: The third author gratefully acknowledges the financial support from FCT Fundação para a. Ciência e a Tecnologia (Portugal), national funding through a research grant from the Information Management Research Centre – MagIC/NOVA IMS (UIDB/04152/2020